Parkinson's Disease and Cognitive-Motor Dual-Task: Is Motor Prioritization Possible in the Early Stages of the Disease? - Ângela Fernandes (2016)
. The authors aimed to compare the postural phase of gait initiation under single-task (gait initiation) and dual-task (gait initiation plus Stroop test) conditions in healthy subjects and in subjects with Parkinson's disease (PD) in the early stages (Hoehn and Yahr scale < 3). The postural phase of gait initiation was assessed through the centre of pressure in single and dual task in 10 healthy subjects and 9 with PD. The analysis indicated that in the early stages of PD, an additional cognitive task did not affect the displacement of the gait initiation. No significant effects occurred between the groups and within-subjects (p > .05). Also, no interaction was found between the groups and the conditions (single- and dual-task). Differences were found in the duration of the mediolateral postural phase (p D .003), which was higher in PD subjects than in healthy subjects. The findings suggest that subjects in the early stages of PD prioritize gait initiation, as their motor performance was similar to that of healthy subjects.